PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN JASA TRANSPORTASI KERETA API SRI LELAWANGSA PADA PT. KERETA API INDONESIA DAERAH OPERASIONAL MEDAN - Mas Intan Purba (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this study was to determine the effect of service quality on satisfaction, the influence of customer satisfaction on loyalty, and the effect of service quality on Sri Lelawangsa Railway service customer loyalty. The sample of this study is 80 people who are Sri Lelawangsa railway transportation service customers. Data that has been collected through questionnaires that have been tested for validity and reliability, then processed using the classical assumption test and multiple regression analysis. Based on the results of the study, it is known that the results of this study are (1) there is a positive and significant influence between Service Quality on Customer Satisfaction, (2) there is a positive and significant influence between Service Quality on Customer Loyalty, (3) there is a positive and significant influence between Satisfaction Customers to Sri Lelawangsa Railway Loyalty Customer Service.